Optimized image segmentation using an improved reptile search algorithm with Gbest operator for multi-level thresholding - Laith Abualigah; Nada Khalil Al-Okbi; Saleh Ali Alomari; Mohammad H. Almomani; Sahar Moneam; Maryam A. Yousif; Vaclav Snasel; Kashif Saleem; Aseel Smerat; Absalom E. Ezugwu (Scientific Reports)
Abstract Image segmentation using bi-level thresholds works well for straightforward scenarios; however, dealing with complex images that contain multiple objects or colors presents considerable computational difficulties. Multi-level thresholding is crucial for these situations, but it also introduces a challenging optimization problem. This paper presents an improved Reptile Search Algorithm (RSA) that includes a Gbest operator to enhance its performance. The proposed method determines optimal threshold values for both grayscale and color images, utilizing entropy-based objective functions derived from the Otsu and Kapur techniques. Experiments were carried out on 16 benchmark images, which included COVID-19 scans along with standard color and grayscale images. A thorough evaluation was conducted using metrics such as the fitness function, peak signal-to-noise ratio (PSNR), structural similarity index measure (SSIM), and the Friedman ranking test. The results indicate that the proposed algorithm seems to surpass existing state-of-the-art methods, demonstrating its effectiveness and robustness in multi-level thresholding tasks.